2014
DOI: 10.1155/2014/391250
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriInfection and Insulin Resistance in Diabetic and Nondiabetic Population

Abstract: Helicobacter pylori (HP) is a common worldwide infection with known gastrointestinal and nongastrointestinal complications. One of the gastrointestinal side effects posed for this organism is its role in diabetes and increased insulin resistance. The aim of this study was to evaluate the association between HP and insulin resistance in type 2 diabetic patients and nondiabetics. This cross-sectional study was carried out from May to December 2013 on 211 diabetic patients referred to diabetes clinic of Shahid Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 26 publications
3
32
0
6
Order By: Relevance
“…These findings are in agreement with previous studies, which hypothesized that HP infection significantly and independently contributed to promoting insulin resistance in diabetic subjects [18,19,37]. This trend toward a possible association between HP infection and insulin sensitivity has been highlighted by a recent systematic review of literature on the topic [14].…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in agreement with previous studies, which hypothesized that HP infection significantly and independently contributed to promoting insulin resistance in diabetic subjects [18,19,37]. This trend toward a possible association between HP infection and insulin sensitivity has been highlighted by a recent systematic review of literature on the topic [14].…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 93%
“…Conflicting in vivo results have been published on this possible relationship between HP and type 2 diabetes [13,14]. Some publications have shown no correlation between HP infection and glucose homeostasis [15][16][17], whereas others have reported that HP infection significantly contributes to promoting insulin resistance [18][19]. Furthermore, the seroprevalence risk of HP infection among patients with diabetes is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other authors investigated a possible role of H. pylori in insulin resistance; on this subject, Vafaeimanesh et al. reported not only a higher prevalence of H. pylori in patients with diabetes, but also a positive association with insulin resistance. While these data perfectly match the results obtained in previous studies , more recently Zhou et al.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Similarly, Horikawa et al [9] showed how H. pylori infection significantly worsens glycemic control in patients with diabetes. Moreover, other authors investigated a possible role of H. pylori in insulin resistance; on this subject, Vafaeimanesh et al [10] reported not only a higher prevalence of H. pylori in patients with diabetes, but also a positive association with insulin resistance. While these data perfectly match the results obtained in previous studies [11], more recently Zhou et al [12] clearly demonstrated that H. pylori infection can induce hepatic insulin resistance by interfering with the c-Jun/miR-203/suppressor of cytokine signaling 3 (SOCS3) pathway both in humans and in an animal model, and another study showed a positive effect of H. pylori eradication on microalbuminuria in patients with DM [13].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Bazı yayınlarda HP infeksiyonu ile glukoz dengesi arasında korelasyon gösterilememiştir (4,5,6). Ancak HP infekksiyonunu anlamlı bir şekilde insulin direnci oluşturduğu bildirilmiştir (3,7,8).…”
Section: Introductionunclassified